Peaky Finders: Characterizing Double-peaked Type IIb Supernovae in Large-scale Live-stream Photometric Surveys - Adrian Crawford; Tyler A. Pritchard; Maryam Modjaz; Craig Pellegrino; Sahana Kumar; Raphael Baer-Way (The Astrophysical Journal)
We present the first photometric population study of double-peaked Type IIb supernovae (SNe IIb). SNe IIb are produced from the core collapse of massive stars whose outermost hydrogen layer has been partially stripped prior to explosion. These double-peaked light curves, consisting of a shock-cooling emission (SCE) peak followed by the main nickel-powered peak, contain more crucial information about the progenitor system than the typical single-peaked light curves. We compiled and analyzed a sample of 14 spectroscopically confirmed SNe IIb—including previously unpublished and reclassified—with publicly available photometric observations, discovered between 2018 and 2022, from the Zwicky Transient Facility and Asteroid Terrestrial-impact Last Alert System surveys. We developed and fit a piecewise linear model, referred to as the “lightning bolt” model, to describe the early-time behavior of these objects to measure population statistics. Notably, we find the SCE peak lasts, on average, fewer than 5 days above half-maximum light, with a mean rise time of 2.07  ±  1.0 and 1.1  ±  0.8 mag day ^−1 in the g and r bands, respectively. These SCE rise rates are over 10× faster than—and last only a third the duration of—the rise to the Ni-powered peak. These rise times are comparable to those of fast blue optical transient events, and we discuss the implications in the text. Finally, we present a proof-of-concept alert filter, using the ANTARES broker, to demonstrate how to translate these population statistics into simple and effective filters to find potential double-peaked SNe IIb in large-scale survey alert streams, like the imminent Vera C. Rubin Observatory Legacy Survey of Space and Time.